Development of a power take-off for wave energy generation - Cardoso, Paulo Alexandre Oliveira (2022)
Currently we face an ever enlarging threat by the environment. Years of pollution have culminated in this situation. One of the biggest sectors contributing for this reality is the energy sector, this when paired up with the ever rising need for electricity can further damage our planet. Fortunately, most countries and other big organizations are aware of this situation, and thus, are providing solutions to transform the energy sector. This can be seen in the rising percentage of electricity produced by renewable sources. However, due to the uncontrollable nature of most Renewable Energy Sources (RES) this percentage may never reach 100%. For this reason it is necessary to diversify our sources. One possible expansion of our current sources might be the wave energy. This source as a very high potential, not just for the large amount of ocean in our planet, but also, due to its relative predictability when compared with most other RES. As it currently stands, this source as only been theorised and as not yet reached any marketable device, only prototypes. For this reason it is important to contribute to this field in order to make this technology more reliable and to diversify our energy sources. This dissertation shows the development of a mechanical Power Take-Off (PTO), based on a rack and pinion gear train, for Wave Energy Converters (WEC), from an initial review of current technology to a ready to produce prototype, detailing every engineering decision.